Evaluation of Various Causes and Treatment of Obstructive Jaundice at Liaquat University Hospital (Medical Forum Monthly, 2024)
Objectives: The purpose of this study is to evaluate various causes of obstructive jaundice and its available treatment modalities in this area.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at Liaquat University Hospital Hyderabad/Jamshoro from January 2010 to december 2010.Materials Methods: All the patients above 15 years of both sexes were included in this study having obstructive jaundice diagnosed on the basis of clinical grounds and supported by LFT and ultrasonography. A uniform system of history taking, physical examination, investigation and treatment was adopted for all the patients and information was recorded on the pre-designed proforma.Results: Comprises 80 cases of obstructive jaundice, average age was 50 years with the female to male ratio1.5:1. The most common cause was carcinoma of head of pancreas in 27 (33.75%) followed by bile duct stone disease in 24(33%) cases of carcinoma of gallbladder were in females. Jaundice with weight loss, itching (46%) and mass (28%) were the presenting features in malignant obstruction while pain (83.33%) and fever (25%) was mostly seen in patient with choledocholithiasis. Gallbladder was palable in malignant obstruction only. Anemia was the common associated problem (60%) especially in malignant cases (83%) only biopsy was preferred in 30 (37.50%) of cases, while choledochoduodenustomy in 14 (17.5%). Postoperative complications were only in 28 (35%) of patients with wound sepsis in 17 (11.25%). The mortality rate was (11.25%). Maximal survival for carcinoma of pancreas was 9 months. The average post operative stay was 12 days.Conclusion: Cholecystectomy with supraduodental choledochotomy and T-tube insertion is effective treatment for bile duct stones whereas internal drainage of billary system is good for advanced malignant cases.